GGE-BIPLOT ANALYSIS FOR GENOTYPE ENVIRONMENT INTERACTIONS IN SOME QUALITY TRAITS OF SILAGE MAIZE GENOTYPES - K. Kokten (Journal of Animal and Plant Sciences, 2020)
Silage maize quality is crucial for yield parameter. However, there is little unknown regarding to GGE-biplot analysis for Genotype-Environment Interactions. For this purpose, experiments were conducted in 6 different environments in randomized blocks design with 3 replications. Effects of genotypes, environments and genotype x environment interactions (GEI) on dry hay yield (DHY) and 8 other quality traits of dry hay [crude protein content (CPC), crude protein yield (CPY), crude ash content (CAC), relative feed value (RFV), dry matter digestibility (DMD), dry matter intake (DMI), acid detergent fiber (ADF) and neutral detergent fiber (NDF)] of 25 silage maize genotypes were investigated. GGE-biplot analysis was used for GEI analysis of 9 traits. Biplot graph axes of the traits were able to explain the least 40.08% of the total variation in CPC and the most 69.6% of the total variation in DHY. It was observed through assessing all traits together that the genotypes of SAFAK and BURAK were placed in ideal genotype section and the genotypes of WAYNE and 30B74 were placed in the stable portion of desirable genotype section for DHY, which is the most significant quality trait in silage maize culture. Besides them, the genotypes, SEME KUKURUZA 877, SEME KUKURUZA 873, DKC 6589 and DKC 7211 were identified as stable genotypes. Furthermore, the genotype 6 was identified as a stable genotype with the best adaptation for ADF, NDF and DMD, the genotype BURAK for crude ash content, the genotype ADV 2898 for crude protein content, the genotype SAFAK for crude protein yield and the genotypes DKC 6590 and DIAN for RFV.
Keywords: crude protein; dry hay yield; GGE-biplot; nutritive quality; silage maize